Death by suicide long after electroconvulsive therapy. Is the sense of coherence test of Antonovsky a predictor of mortality from depression? - John Erik Berg (Mental Illness)
Prediction of increased risk of suicide is difficult. We had the opportunity to follow up 20 patients receiving electroconvulsive therapy (ECT) because of severe depression. They filled in the Antonovsky sense of coherence test (SOC) and Beck depression inventory (BDI) before and after a series of ECT treatments. Seventeen surviving patients had a mean observation time of 20.6 months, whereas the three deceased patients had 11.3 months. There was a lower mean age at onset of illness and a longer mean duration of disease in the deceased. Other clinical parameters did not differ. The surviving patients had a significant decrease on the BDI from 35 to 18 (P less than 0.001) and an increase on the SOC test after ECT from 2.45 to 3.19 (P less than 0.001), indicating both less depression and better functioning in life. The deceased had a larger change on the BDI from 32 to 13, not attaining significance because of the low number of deceased. The SOC test, however, did not increase to a purported normal level; that is, from 2.43 to 2.87. Although the SOC scale has been shown to predict mortality in substance abusers, the SOC test has not been part of earlier reviews of predictive power. Tentatively, a low pathological score on the SOC test may indicate low sense of coherence in life that might increase the propensity for suicide. These preliminary results need replication in larger studies.